Secondary consolidation characteristics of organic soil modified by bio-enzyme based on the Gibson model - Zhang, Yixin; Wen, Changping (Frontiers in Materials, 2022)
In order to study the secondary consolidation characteristics of organic soil improved by bio-enzyme, the secondary consolidation test was carried out. First, the Gibson rheological model parameters were fitted according to the experimental results. Then, the relationship between rheological model parameters, Ca/Cc value, secondary consolidation coefficient Ca, and load was analyzed for different ratios of bio-enzyme. The results showed that: 1) the rheological model parameters were negatively correlated with the ratios of bio-enzyme and positively correlated with the load value. The rheological model parameters E1 (Kelvin elastic modulus) and η (Kelvin viscosity coefficient) reached the maximum value when the ratio of bio-enzyme was 0.01%. 2) The secondary consolidation coefficient was related to the load and showed a certain law. At 100 kPa, the secondary consolidation coefficient of samples reached the peak. When it was less than 200 kPa, the secondary consolidation coefficient changed obviously with the increase in load. When the load was greater than 200 kPa, the variation trend of the secondary consolidation coefficient tended to be gentle with the increase in load and finally tended to be constant. With the increase in load, the secondary consolidation coefficient Ca finally approached to a stable value. 3) The value of Ca/Cc of improved organic soil varied from 0.042 to 0.1 under various loads. In this article, the secondary consolidation characteristics of organic soil modified by bio-enzyme were studied. The secondary consolidation strain can be predicted by the established rheological model parameter equations.